The Effect of Psycho-Education Combined with Social Media Program on Symptom Severity of Persons with Bipolar Disorder - สมตน, ศิริมา; อังสุโรจน์, ยุพิน; สุขตระกูล, สุนิศา (Journal of The Royal Thai Army Nurses, 2019)
This research is a quasi-experimental research design were used nonequivalent comparison-group design. The objectives were to compare symptom severity of patients with bipolar disorder before and after receiving the psycho-education combined with social media program and compare symptom severity of patients with bipolar disorder after receiving the psycho-education combined with social media program to patients who are received regular nursing care. The samples were 40 patients with bipolar disorder who were the out patients of Nakornratchasima Rajanagarindra Psychiatric Hospital. The patients were matched pair with genders, depression level scores, and mania level scores, and also samples to experimental group, consisting of 20 subjects while the control group of 20 subjects. The research instruments comprised: 1) psycho-education combined with internet supported program, 2) Brief Bipolar Disorder Symptom Scale, 3) Knowledge on Bipolar Disorder Test, 4) Self-management Interview for Bipolar Disorder, 5) Hamilton Rating Scale for Depression, and 6) Thai Mania Rating Scale. All instruments had been validated the content from five experts. The validity, Cronbach’s alpha coefficient of instrument 2 was .85 respectively. T-test was used to analyze data. The results showed that symptom severity of patients with bipolar disorder after receiving the psycho-education combined with social media program was lower than before receiving the program at a .05 level of significance and symptom severity of patients with bipolar disorder receiving the psycho-education combined with social media program was lower than the patients who were received regular nursing care at a .05 level of significance